Strengthening the Role of Village Head Communications In The Digital Age - Andre Novie Rahmanto, Edy Sutrisno, Ismi Dwi Astuti Nurhaeni dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The village head as a local actor has a strategic role in the development andempowerment of village communities. The implementation of Law No. 6 of 2014on Villages as well as Law Number 14 Year 2008 on PublicInformation Transparency is a demand that must be responded by the village head.Moreover, the third point of Nawacita: